STRATEGY OF MSMEs DEVELOPMENT IN FACING THE INDUSTRIAL ERA 4.0: IN THE ACCOUNTING PERSPECTIVE - Dendy Syaiful Akbar; Eva Faridah; Mohamad Apip; Roni Marsiana Suhendi (Universitas Galuh, 2019)
The purpose of this study is to analyze the ability of MSMEs to improve industrial competitiveness and strategies to improve industrial competitiveness in the context of facing the industrial era 4.0 in an accounting perspective. The research method uses descriptive methods that are explorative in nature. The data analysis technique uses descriptive analysis techniques, which are carried out by describing the facts of the findings and presenting them by providing sufficient understanding and explanation. The results of the study show that the MSMEs sector in Indonesia has not been able to improve competitiveness in the face of the industrial era 4.0 from an accounting perspective. Meanwhile, the strategy that can be utilized by MSMEs in facing the current digital era seen from an accounting perspective is by utilizing the Government budget for MSMEs development programs, utilizing credit facilities and empowerment from banks, and utilizing technological advances.